CRIMINAL LIABILITY AGAINST PERSONS OF AUTHENTIC DEED FORGERY (Study Decision Number: 1611/Pid.B/2014/Pn.Mks) - Aflinda, Devi Evany; Rahman, Sufirman; Djanggih , Hardianto (IBLAM LAW REVIEW, 2024)
This research aims to (1) determine and analyze the forms of criminal responsibility and legal considerations of judges regarding the forgery of authentic deeds based on false statements in Makassar District Court Decision Number: 1611/Pid.B/2014/PN.Mks. (2) knowing and analyzing the legal consequences arising from authentic deeds that are based on false information. This research was conducted in Makassar, South Sulawesi Province, specifically at the Makassar District Court. This research was carried out by taking data from copies of decisions regarding the criminal act of ordering to place false information in authentic deeds. Apart from that, the author also conducted literature studies by reviewing books, literature and statutory regulations related to the problems. The result obtained is that the application of material law, in this case, is not appropriate because the element of the article being accused, namely Article 266 paragraph (1), which, in the author's opinion, is not appropriate the element of the use of the deed can cause harm, whereas the use of an authentic deed does not provide the damages alleged are selected by the Panel of Judges. Furthermore, the decision-making process carried out by the Panel of Judges, in the author's opinion, is not following the applicable legal rules because one of the elements in the article being charged is not following the facts in the trial. So, according to the author, imposing a crime on the defendant is inappropriate both in the Court of First Instance and the High Court.